International organizations, European Union access, and authority - Alexandros Tokhi (Journal of European Integration, 2022)
In recent years, the European Union has gained access to several international organizations (IOs). This is a noteworthy and novel development, as IOs not only formalize but also deepen their interactions with the EU by granting it formal rights to participate in their policymaking processes. Building on the literature on the EU's role in global governance and the opening-up of IOs, this paper investigates the conditions under which IOs grant the EU access to their decision-making processes. While overlapping policy mandates between the concerned IO and the EU are certainly an important explanation, they are not the entire story. As this paper suggests, much depends on the authority of the IO granting access to the EU. This is because the members of authoritative IOs recognize in the EU a highly authoritative IO and might thus be more inclined to take it on board in order to mitigate negative externalities, enhance their own effectiveness, and avoid intra-institutional conflicts. Using a novel dataset on the EU's formal access to 33 IOs and addressing important inferential concerns, the statistical analysis shows that EU access depends on the authority of IOs. That authoritative IOs establish formal relations between themselves provides the basis for increased interactions and opportunities to jointly shape global outcomes.
Keywords: 320; European Union; access; authority; international organizations